Efficacy and safety of gemcitabine plus erlotinib for locally advanced or metastatic pancreatic cancer: a systematic review and meta-analysis - Wang Y; Hu GF; Zhang QQ; Tang N; Guo J; Liu LY; Han X; Wang X; Wang ZH (Dove Medical Press, 2016)
Yuan Wang,1 Guo-fang Hu,1 Qian-qian Zhang,1 Ning Tang,1 Jun Guo,2 Li-yan Liu,2 Xiao Han,2 Xia Wang,2 Zhe-hai Wang2 1School of Medicine and Life Sciences, Shandong Academy of Medical Sciences, University of Jinan, 2Shandong Cancer Hospital, Shandong University, Jinan, Shandong, People’s Republic of China Background: Pancreatic cancer is considered as a chemoresistant neoplasm with extremely dismal prognosis. Gemcitabine is recommended as the standard agent for locally advanced or metastatic pancreatic cancer. A series of trials have been conducted to improve the outcome of advanced pancreatic cancer with other anticancer drugs in combination with gemcitabine. Unfortunately, the designers of the clinical trials failed to improve the poor prognosis of patients with advanced pancreatic cancer. Erlotinib was the first additional drug that improved the overall survival of patients with advanced pancreatic cancer with gemcitabine. We performed this systematic review and meta-analysis to explore the efficacy and safety of the combination of gemcitabine with erlotinib (GemErlo) for patients with advanced pancreatic cancer using the currently available evidence. Methods: PubMed/MEDLINE, EMBASE, the Cochrane Library, and relevant abstracts of major conferences were comprehensively searched. Data results on objective response rate, disease control rate, and 1-year survival were pooled by using MetaAnalyst with a random-effects model. Results on progression-free survival and overall survival were only summarized descriptively. Results: A total of 24 studies with 1,742 patients with locally advanced or metastatic pancreatic cancer treated with GemErlo were included. Combined objective response rate was 14.4% (95% CI: 11.6%–17.7%), disease control rate was 55.0% (95% CI: 51.5%–58.5%), and 1-year survival rate was 28.5% (95% CI: 24.0%–33.4%). Progression-free survival ranged from 2.63 to 9.6 months, and overall survival varied from 6 to 10 months. As for the toxicity profile, the most common adverse events (AEs) were hematologic reactions, skin rash, and gastrointestinal reactions. Other severe AEs, which had low incidence, included treatment-induced death and interstitial lung disease. Conclusion: Our study showed that GemErlo is associated with reasonable activity in treating patients with locally advanced or metastatic pancreatic cancer. Most of the AEs were tolerable, while some severe AEs needed careful detection. Keywords: advanced pancreatic cancer, chemotherapy, targeted agent, meta-analysis